Investigation of the axial compressive behavior of Kevlar fibers using the dynamic loop test. Issue 18 (September 2019) - Abuobaid, Ahmad; Ganesh, Raja; Gillespie, John W
A dynamic loop test method for measuring strain rate-dependent fiber properties was developed. During dynamic loop testing, the fiber ends are accelerated at constant levels of 20.8, 50 and 343 m/s 2 . The test method is used to study Kevlar® KM2-600, which fails in axial compression due to kink band formation. The compressive failure strain and strain rate at the onset of kink band formation is calculated from the critical loop diameter ( D C ), which is monitored throughout the test using a high-speed camera. The results showed that compressive failure strain increases with strain rates from quasi-static to a maximum strain rate of 116 s −1 by a factor of ∼3. Kink angles (φ) and kink band spacing ( D S ) were 60 ° ± 2 ° and 16 ± 3 μm, respectively, over the strain rates tested. Rate-dependent mechanisms of compressive failure by kink band formation were discussed.